The impact of ESG ratings on implied and historical volatility - Eric Burger; Fabian Grba; Thomas Heidorn (Frankfurt School of Finance & Management, 2022)
The economic and political developments of the past years show an increasing importance of a possible risk-reducing of the company due to good ESG performance. Our work contributes by examining the impact of relatively better ESG performance of companies on their implied and historical share volatility. Our regressions show a clear relationship between the volatilities and the ESG ratings of the market-leading agencies (Bloomberg, Refinitiv, Sustainalytics and MSCI) and our combined score. A better ESG performance measured by the company's ESG rating(s) has a risk-reducing effect in the form of lower stock volatility. However, our combined rating has the strongest impact.
Keywords: G11; G24; G32; Q56; 330; Environmental; Social and Governance (ESG); ESG Ratings; ESG Rating Filter; Equity Volatility; Historical Volatility; Implied Volatility; Company Risk Performance